Use of magnesium-silicate-hydrate (M-S-H) cement mixes in 3D printing applications. (March 2021) - Panda, Biranchi; Sonat, Cem; Yang, En-Hua; Tan, Ming Jen; Unluer, Cise
Abstract: This study focused on the development of 3D printed building components incorporating MgO–SiO2 binders. The effects of parameters such as MgO/SiO2 and water/binder ratios and superplasticizer dosage were evaluated to produce 3D printable MgO–SiO2 binders. The assessment of rheological and mechanical properties, which led to an optimum mix that satisfied the printability criteria, was supported by microstructural characterization. The best-performing mix in terms of printability and mechanical performance was characterized via x-ray diffraction (XRD), thermogravimetric analysis/derivative thermogravimetry (TG/DTG) and field emission scanning electron microscopy (FESEM) with energy dispersive spectroscopy (EDS). The selected mix exhibited thixotropic behaviour with an ability to recover 80% of its original viscosity within 60 s of extrusion and a shape retention factor of 1. The extrudability, shape retention and buildability aspects were successfully demonstrated by printing a 5-layered 3D structure without any deformations. The final product contained brucite and M-S-H as hydration products, which were the main contributor to mechanical performance and microstructural densification.